DIVERSITY OF HERPETOFAUNA SPECIES AT THE SECTION I OF ALAS PURWO NATIONAL PARK , BANYUWANGI, EAST JAVA - Bayu Wisnu Broto; Subeno Subeno (Widyariset, 2012)
The existence of herpetofauna at the Alas Purwo National Park has been neglected. It has been shown bythe lack of diversity data of herpetofauna in the National Park. This research was aimed to inventory and identifyof herpetofauna at Section I of the Alas Purwo National Park Management (SPTN I) for determination of thediversity level (H’). Evenness Index (E), and Simpson Domination Value (D) were used in this research Observationfound 4 families of amphibian with 1.486 samples and 7 families of reptile with 90 samples. SPTN I AlasPurwo National Park was considered as a medium level of diversity with 1.93 of H value. The research suggeststhat SPTN I belongs to a middle diversity level, middle evenness index, and relatively low domination value.